The Afterlife of Christina Rossetti - Chapman, A. author. aut Link
XI, 213 p.
Keywords: Despite new historical study of her contexts, Christina Rossetti continues to haunt the reader as a displaced subjectivity emptied of history. Through an analysis of the posthumous in her work, the construction of 'Christina Rossetti' by her brothers, and the history of reception, this study asks how 'speaking with the dead' can avoid critical ventriloquy. The figure of the mother is offered as a paradigm for theorising a new reading that refuses to exorcise the ghost of 'Christina Rossetti'.